Golf shot performance analysis: the effects of ground slope on weight transfer and shot characteristics - Gerçek, N.; Uzun, S.; Tatar, Y.; Asan, I. G.; Göçmez, H. B.; Kahraman, M. Y. (International Journal of Performance Analysis in Sport, 2025)
The aim of this study was to examine the elite golf players` centre of force (COF) displacements and golf shot performance during golf shots on three different ground inclinations. Twenty elite golf players were asked to hit golf shots on flat surface, 10° uphill and 10° ball above feet using their six irons. COF displacements (TekScan MatScan® force platform) and golf shot performance (TrackMan® golf radar system) were analysed. In this study, golf players` weight transfer was similar in each shot (p > 0.05), except higher A-P sway during the ball above feet golf shots (p < 0.05). Reduced control of balance during shots from ball above feet resulted in shorter shot length than flat surface, even if the angles of attacks were similar (p < 0.05). In addition, increased COF distance during flat ground and ball above feet golf shots improved clubhead speed and shot length (p < 0.05). These results show that ball above feet slope condition, rather than uphill, alters postural control and golf swing characteristics. In order to improve the performance of these shots, it is recommended to add balance training and weight transfer techniques in A-P direction to the training programmes.